Efektivitas Pendaftaran Tanah Sistematis Lengkap (PTSL) Hak Atas Tanah - Istiana, Atiqah (Sovereign: International Journal of Law, 2023)
This study aims to analyze the effectiveness of the implementation of Complete Systematic Land Registration (PTSL) of Land Rights at the Land Office of Takalar Regency, and the factors that influence it. This type of research is empirical legal research with a quantitative descriptive in nature. This research was conducted at the Land Office of Takalar Regency. The data collection techniques used in this study were questionnaires, documentation, and literature study. The data analysis technique used is quantitative data analysis techniques. The results showed that the implementation of Complete Systematic Land Registration (PTSL) of Land Rights at the Land Office of Takalar Regency was effective. Factors that influence the implementation of PTSL are the legal structure factors; community legal culture factors; as well as legal facilities/infrastructure factors. It is hoped that the officers at the Land Office of Takalar Regency will be more active in providing legal counseling so that the public knows the benefits of PTSL, namely providing legal certainty, certainty of registered rights status, certainty of rights to objects, and providing understanding that land title certificates can improve the community’s standard of living, especially as business capital.